Bourne's Quest For Identity In Dough Liman and Paul Greengrass's Bourne Trilogy Movies (The Bourne Identity, The Bourne Supremacy and The Bourne Ultimatum) : An Existentialist Criticism - KURNIAWATI, DWI (2012)
This study is aimed to show the Bourne‟s Quest for Identity in the Bourne Trilogy Movies by using Existentialist criticism. It is done by establishing two objectives: the first is analyzing the movies based on its structural elements and the second is analyzing the movies based on the existentialist analysis. This reserach is descriptive qualitative research. In this method, the writer uses two types of data source, namely primary and secondary. The primary data source is the films and manuscripts of the Bourne Trilogy movies (The Bourne Identity, The Bourne Supremacy and The Bourne ultimatum) directed by Doug Liman and Paul Greengrass released in 2002, 2004 and 2007. While the secondary one is any literature related to this study for example reading some other resources related to the movies. Both data are collected through library research and analyzed by descriptive analysis. The study comes to the following conclusions. First, based on the structural analysis of each elements, it shows that the character and characterization, plot, setting, point of view, theme, casting, mise-en-scene, cinematography, sound and editing are related to each other and form the unity. Second, based on the existentialist analysis, Doug Liman and Paul Greengrass want to convey a moral message that identity is needed by every human to determine the course and the purpose of life. These movies also criticizes that human is not a machine or robbot which can be commanded everytime based on what their boss want.